2015
DOI: 10.1039/c5ra02057c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic solvent and Brønsted acid on 5-hydroxymethylfurfural preparation from glucose over CrCl3

Abstract: In the present work, the influence of organic solvent on the mechanism of 5-hydroxymethylfurfural (HMF) preparation from glucose over CrCl 3 and the role of Brønsted acid (N-methyl-2-pyrrolidone hydrogen sulfate ([NMP]HSO 4 ), N-methyl-2-pyrrolidone bromide ([NMP]Br), N-methyl-2-pyrrolidone chlorine ([NMP]Cl), H 2 SO 4 , HBr and HCl) during the reaction were researched by a complementary computational and experimental study. It was found that dimethyl sulfoxide (DMSO) gave the lowest conversion of glucose by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The theoretical calculations could also be used to elucidate the interactions between carbohydrates and metal ions. Nevertheless only a few studies are reported in the literature, which include the molecular dynamics studies on Na +glucose interactions [26], computational evidence for the complex formation between Cr 3+ [27], and Cr 2+ [28] with glucose. Furthermore, only a handful of studies have attempted to address the mechanisms of metal promoted depolymerization and dissolutions of cellulose [29].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical calculations could also be used to elucidate the interactions between carbohydrates and metal ions. Nevertheless only a few studies are reported in the literature, which include the molecular dynamics studies on Na +glucose interactions [26], computational evidence for the complex formation between Cr 3+ [27], and Cr 2+ [28] with glucose. Furthermore, only a handful of studies have attempted to address the mechanisms of metal promoted depolymerization and dissolutions of cellulose [29].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In comparison with other sugars, glucose is the most abundant hexose contained in lignin biomass, considered as the most valuable bio-derived carbon resource, and it plays a vital role in the conversion of biomass to biofuels and chemicals. [3][4][5] Thus, the high-efficiency transformation of glucose to platform chemicals has aroused much attention in recent years. 6 Among those prospective chemicals, HMF and EMF are thought highly of as promising building blocks for the application of renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…In Yan's work, CrCl 3 showed excellent catalytic efficiency in the conversion of carbohydrates. 34 But as it known to us, Cr belongs to heavy metal and do harm to the environment with some toxicity. Recently, via the good deal of work of Yu Yang and Hu, Li, AlCl 3 $6H 2 O was also proved to be a preeminent catalyst in the production of EMF, high yield with expectation achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 5-Hydroxymethylfurfural (HMF), a dehydration product of C 6 carbohydrates, is one of the 10 most value-added bio-based platform chemicals, as it can be used in the synthesis of chemicals and liquid fuels. 6 HMF production from glucose mainly comprises two steps, namely, isomerization of glucose to fructose and dehydration of fructose to HMF. Production of HMF using fructose as feedstock has high yield, but the limited sources and high price of fructose restrict the large-scale application of this process.…”
Section: Introductionmentioning
confidence: 99%